Adherence to General Diabetes and Foot Care Processes, with Prompt Referral, Are Associated with Amputation-Free Survival in People with Type 2 Diabetes and Foot Ulcers: A Scottish National Registry Analysis. (14th June 2022) - Meza-Torres, Bernardo; Cunningham, Scott G.; Heiss, Christian; Joy, Mark; Feher, Michael; Leese, Graham P.; de Lusignan, Simon; Carinci, Fabrizio
Abstract : Aims . To compare different packages of care across care providers in Scotland on foot-related outcomes. Methods . A retrospective cohort study with primary and secondary care electronic health records from the Scottish Diabetes Registry, including 6, 845 people with type 2 diabetes and a first foot ulcer occurring between 2013 and 2017. We assessed the association between exposure to care processes and major lower extremity amputation and death. Proportional hazards were used for time-to-event univariate and multivariate analyses, adjusting for case-mix characteristics and care processes. Results were expressed in terms of hazard ratios with 95% confidence intervals. Results . 2, 243 (32.7%) subjects had a major amputation or death. Exposure to all nine care processes at all ages (HR = 0.63 ; 95% CI: 0.58-0.69; p < .001 ) and higher foot care attendance in people aged >70 years (HR = 0.88 ; 0.78-0.99; p = .03 ) were associated with longer major amputation-free survival. Waiting time ≥ 12 weeks between ulceration and clinic attendance was associated with worse outcomes (HR = 1.59 ; 1.37-1.84; p < .001 ). In people > 70 years, minor amputations were associated with improved major amputation-free survival (HR = 0.69 ; 0.52-0.92; p = .01 ). Conclusions . Strict adherence to a standardised package of general diabetes care before foot ulceration, timely foot care after ulceration, and specific treatment pathways were associated with longer major amputation-free survival among a large cohort of people with type 2 diabetes in Scotland, with a larger impact on older age groups.